Atypical Accommodations for Employees with Psychiatric Disabilities. (3rd August 2018) - Hickox, Stacy A.; Hall, Angela
Abstract : People with psychiatric disabilities often need atypical accommodations to participate in today's workforce. Some of these accommodations, including structural and social changes in the workplace, can address biases against people with psychiatric disabilities, while others ameliorate deficits that may affect performance or interaction with others. Many courts have denied requests for such accommodations based on employers' assumptions about performance or the direct threats purportedly posed by people with psychiatric disabilities. By challenging these assumptions, which can be influenced by stigma and stereotypes, and by enforcing an employer's duty to interact regarding potential accommodations, employees with psychiatric disabilities could benefit from structural and social accommodations. Courts should consider social science research in determining which nontraditional accommodations may be reasonable and whether the employer can establish that they impose any undue hardship. Such consideration will expand opportunities for people with psychiatric disabilities in the workplace without unduly interfering with employers' interests.